Plan de negocios para la creación de un centro de impresiones fotográfica digitales en el cantón Quinsaloma provincia de Los Ríos, año 2013 - Romero Manjarrez, Enrique Javier (2012)
This research was conducted in the Canton Province Quinsaloma Rivers, in the area of business services, same that focuses on the analysis of the cultural significance of the study population, revealing the scope of purchase intent the products, processes leading to define the target that is directed to the service to be offered. The Company current product development achieved in science and technology, requires employers is formed in the field of Market aspects, knowledge bases that will promote sustainable development of the productive apparatus. These processes are generated by the presence of diverse social, ethnic and cultural that occurs with the arrival of hundreds of companies, that his business is focused on the exploitation of the field Agricultural, Commercial, Industrial and Services. The aim of the research is focused on performing market analysis to determine the feasibility and testing of the hypothesis that involves the creation of a Center for Digital Photographic Prints Quinsaloma in Canton. The proposed methodology for the development of research, noted for its viability in the application and essentially seeks leverage in the formation process of the body that is linked to the productive exploitation; includes principles and appropriate action system for the implementation of the proposal. The results, product research, was the source for Designing a Business Plan for the creation of a Center for Digital Photographic Impressions in Canton Quinsaloma as a tool for sustainable development of the company. To justify the approach of the proposal, from the practice, the study shows a net present value NPV of $ 16.928,53 dollars means that the operation of the service market is representative for the firm. Economic analysis of investment in the implementation and execution of proposed capital projects to recover in five years at an internal rate of return of 31%, economic indicator that determines the opening of business as business is justified. The impact on the context, after putting into execution the proposal, it was estimated that in a short term cover unmet market demand.